Religiosity Rejected: Exploring the Religio-Spiritual Dimensions of Landmark Education - Lockwood, Renee (International Journal for the Study of New Religions, 2011)
As the descendant of Werner Erhard’s 1970s Human Potential group est (Erhard Seminars Training), Landmark Education has continuously denied being a religious organization. Despite ample discourse on the religious nature of the group within popular online and print media, a conspicuous void within academia - particularly within Religious Studies - speaks volumes. Rarely are the boundaries of what constitutes a ‘religion’ expanded in order to explore those groups that, though not understood to be ‘religious’ in a traditional sense, clearly contribute to contemporary ’spiritual’ life. And yet, that Landmark Education is perceived as being somehow religious demands deeper analysis. This article highlights the problematics of ’religion’ within late Western modernity as illustrated by the contention surrounding the religious status of both Scientology and Transcendental Meditation. A discussion of Landmark Education is offered in light of these issues, along with a dissection of the religio-spiritual dimensions of the organisation and its primary product, the Landmark Forum. Incorporating several eastern spiritual practices, the highly emotional nature of the Landmark Forum’s weekend training is such as to create Durkheimian notions of ’religious effervescence’, altering pre-existing belief systems and producing a sense of the sacred collective. Group-specific language contributes to this, whilst simultaneously shrouding Landmark Education in mystery and esotericism. The Forum is replete with stories of miracles, healings, and salvation apposite for a modern western paradigm. Indeed, the sacred pervades the training, manifested in the form of the Self, capable of altering the very nature of the world and representing the ’ultimate concern’.